Peran Pasar Dalam Distribusi Sumber Daya Perspektif Ekonomi Syariah - Eka Rahayu, Annisa; Athoillah, Mohamad Anton (Jurnal Iqtisaduna, 2022)
The existence of markets has a very important function. For consumers, the existence of markets will make it easier to obtain goods and services of daily necessities. As for producers, the market is a place to facilitate the distribution of goods produced. In general, the market has three main functions, namely as a means of distribution, price formation, and as a place of promotion. One function is as a distribution or allocation of resources. The market has an important role in allocating resources efficiently. There are several ways for the market to allocate resources efficiently. Of course the implementation of resource allocation carried out by the market must be in accordance with Islamic principles and corrections. This can be done so that the market does not fail.